2019
DOI: 10.1002/anie.201907278
|View full text |Cite|
|
Sign up to set email alerts
|

Dynamics of Synthetic Membraneless Organelles in Microfluidic Droplets

Abstract: Cells can form membraneless organelles by liquid–liquid phase separation. As these organelles are highly dynamic, it is crucial to understand the kinetics of these phase transitions. Here, we use droplet‐based microfluidics to mix reagents by chaotic advection and observe nucleation, growth, and coarsening in volumes comparable to cells (pL) and on timescales of seconds. We apply this platform to analyze the dynamics of synthetic organelles formed by the DEAD‐box ATPase Dhh1 and RNA, which are associated with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
73
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 68 publications
(80 citation statements)
references
References 31 publications
7
73
0
Order By: Relevance
“…Linsenmeier et al developed a droplet-based microfluidics by introducing a hydrogel matrix to mimic the cytoskeleton for studying the dynamics of synthetic membraneless organelles of artificial cells (shown in Figure 5A). They observed the nucleation, growth, and coarsening in volumes comparable to cells, and they found that the timescale of phase separation decreases linearly as the volume of compartment increases [120].…”
Section: Hydrogel Droplet For Biomedical Cell Encapsulation and Analysismentioning
confidence: 99%
See 1 more Smart Citation
“…Linsenmeier et al developed a droplet-based microfluidics by introducing a hydrogel matrix to mimic the cytoskeleton for studying the dynamics of synthetic membraneless organelles of artificial cells (shown in Figure 5A). They observed the nucleation, growth, and coarsening in volumes comparable to cells, and they found that the timescale of phase separation decreases linearly as the volume of compartment increases [120].…”
Section: Hydrogel Droplet For Biomedical Cell Encapsulation and Analysismentioning
confidence: 99%
“…The biomedical application of high-throughput biomedical microfluidic systems (HTBMS) with ECM. (A) A droplet-based microfluidic system was developed by introducing a hydrogel matrix mimicking the cytoskeleton to synthetic membraneless organelles, reproduced with permission from[120]. (B) A combinatorial drug screening system was developed based on 3D-cultured cells.…”
mentioning
confidence: 99%
“…These organelles, which lack membrane boundaries, are formed by liquid–liquid phase separation of proteins and nucleic acids, and are involved in several biological functions and dysfunctions . Most of the proteins associated with these compartments contain low complexity domains (LCDs) or low complexity sequences (LCSs), which are intrinsically disordered domains enriched in specific amino acids . In contrast to complex coacervates, which largely rely on electrostatic interactions, these sequences tune a variety of weak, attractive intermolecular interactions that compete with the entropic cost associated with de‐mixing .…”
Section: Figurementioning
confidence: 99%
“…The PhaseScan platform presented herein achieves this objective and allows for the rapid (<5 min), high-throughput, and high-resolution examination of protein LLPS phase behaviour, thereby complementing and expanding upon previous examples of microfluidic investigation of LLPS. 26,29 PhaseScan utilises combinatorial droplet microfluidics to rapidly generate a large number of compartments, each of which can be considered a discrete microenvironment to study protein LLPS. By altering the input solution conditions, a broad range of phaseseparation environments are produced rapidly in order to map LLPS behaviour over a wide region of chemical space.…”
Section: Introductionmentioning
confidence: 99%